2023
DOI: 10.3389/fmicb.2023.1160551
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma and its role in biological control of plant fungal and nematode disease

Abstract: Trichoderma is mainly used to control soil-borne diseases as well as some leaf and panicle diseases of various plants. Trichoderma can not only prevent diseases but also promotes plant growth, improves nutrient utilization efficiency, enhances plant resistance, and improves agrochemical pollution environment. Trichoderma spp. also behaves as a safe, low-cost, effective, eco-friendly biocontrol agent for different crop species. In this study, we introduced the biological control mechanism of Trichoderma in plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(29 citation statements)
references
References 194 publications
0
12
0
3
Order By: Relevance
“…Rhizoctonia solani, Pythium aphanidermatum, Sclerotinia sclerotiorum, and Colletotrichum spp., which are all controlled by the Trichoderma spp. [71]. A study by Paulitz et al [72] demonstrated the efficiency of T. harzianum in reducing Pythium damping-off of cucumbers in greenhouse experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Rhizoctonia solani, Pythium aphanidermatum, Sclerotinia sclerotiorum, and Colletotrichum spp., which are all controlled by the Trichoderma spp. [71]. A study by Paulitz et al [72] demonstrated the efficiency of T. harzianum in reducing Pythium damping-off of cucumbers in greenhouse experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies had demonstrated that Trichoderma strains could inhibit pathogenic fungi through nutrient and spatial competition, hyperparasitism, and the production of antimycotic secondary metabolites, while they could also promote plant growth and enhance plant stress resistance [35]. Ecological niche competition is a crucial mechanism of biocontrol microorganisms for preventing disease in biocontrol.…”
Section: Biocontrol Mechanism Of T Asperellum Cmt10mentioning
confidence: 99%
“…Apabila dilihat peningkatannya, jumlah bunga dari semua perlakuan tanaman masih dapat bertambah (Gambar 4a (Kacprzak et al, 2014), bawang merah pada cekaman tembaga (Téllez et al, 2017), bunga matahari pada cekaman toksisitas timbal (Devi et al, 2017), jagung pada cekaman kadmium (He et al, 2021), serta Brassica juncea pada cekaman kadmium dan arsenik (Yao et al, 2023).…”
Section: Hasil Dan Pembahasanunclassified